Antimicrobial properties of different types of honey and effects of tualang honey as a marinating agent and vacuum packaging on chicken - Mohamed, Khadra Yousuf (2018)
The antimicrobial activity of honey is mainly credited to its acidity, osmolarity and enzymatic generation of hydrogen peroxide via glucose oxidase. Additional honey components, such as aromatic acids or phenolic compounds, might also contribute to the overall antimicrobial activity. The level of antimicrobial activities found in honey varies with different types of honey, and these differences are mainly due to the composition, percentage as well as the nature of the sugars present in the honey. Chicken meat is widely consumed, and it is the most common and popular poultry species in the world. The diverse nutritional composition of chicken meat makes it an ideal environment for the growth and propagation of meat spoilage microorganisms and common foodborne pathogens. It is therefore essential that adequate preservation is applied to maintain its safety and quality. Due to the widespread of antibiotic resistance there is a need to replace modern chemical medicines and preservatives with safer natural remedies to increase the shelf life of chicken. The antimicrobial properties of local (Malaysia) honey are still very limited. Chicken is a perishable commodity, application of honey as a natural preservative could increase the shelf life. The aims of this study were therefore (i) to evaluate the antimicrobial activity of four types of honey namely Tualang Honey (TH1), Tualang Honey (TH2), Acacia Honey (AH) and Yemeni Sumur Honey (YSH), and (ii) to evaluate the effect of honey marinated chicken in different packaging on the microbiological and physicochemical characteristics. Nine bacterial strains were used. Disc Diffusion Assay, Well Diffusion Assay, Minimum Inhibitory Concentration (MIC), Minimum Bactericidal Concentration (MBC) and time-kill methods were performed to reveal the antimicrobial potentials of the honey samples. The diameter of inhibition zone (DIZ) was between 11.17 mm to 35.50 mm for 12.5, 25 and 50% (w/v), respectively. The MIC ranged between 12.5 to 50% for both TH1 and YSH while for TH2, and AH it ranged between 25 to 50%. For MBC, it ranged from 25 to 50%. The time-kill with TH1 of Staphylococcus aureus (food isolate) was 6 h in 2 × MIC and for S. aureus ATCC 29737 was 3.84 log CFU/g at 6 h. For TH2 and AH, the time-kill was decreased from 7 to 5 log CFU/g. While for YSH S. aureus (food isolate) at 2 × MIC was decreased from 6.42 to 3.68 log CFU/g in 6 h, for S. aureus ATCC 29737 at 1× MIC it was decreased from 6.66 to 5.16 log CFU/g and for the 2 × MIC it reached 4.26 log CFU/g at 6 h, for Salmonella Typhimurium ATCC 13311 at 2 × MIC was decreased from 6.56 to 3.83 lo CFU/g at 6 h. Physicochemical quality of honey resulted as follows: the pH of the honey samples were acidic ranging from 3.69 to 3.94, and the aw of the honey samples were between 0.53 to 0.69. For colur analysis, maximum lightness and yellowness were seen in YSH, and maximum redness was seen in TH1, while AH had minimum lightness, redness, and yellowness. For the marinated chicken at different temperatures (25, 10 and 5°C) overall 5°C with vacuum packaging showed increased shelf life and less microbial count for S. aureus, Salmonella Typhimurium and Escherichia coli. While Listeria monocytogenes was not detected in any of the marinated chicken. Therefore, honey marinated chicken with vacuum packaging (HCVP) treatment might be used as an alternative preservative method for storage of chicken and could be recommended to be used for other poultry. The remarkable inhibitory activity of honey might attribute them as potential antimicrobial agent and natural preservative.